The wheat HSF transcription factor TaHSFC3B confers drought tolerance through ROS scavenging and ABA pathway in transgenic Arabidopsis and wheat (Triticum aestivum L.) - Yaning Bu; Tianqi Song; Jianfei Zhou; Xinpeng Lei; Xiling Chang; Siyi Li; Yuxin Wang; Xiaoxing Wang; Ling Kang; Dongsheng Chen; Jishan Xiang; Xiaoke Zhang (Planta, 2025)

SLIT3 knockdown inhibited TGF-β-induced hepatic stellate cells activation by down-regulating YAP signal - Xiling Fu; Jiabao Chang; Damin Jiao; Mengying Zhu; Yuqi Ma (Molecular & Cellular Toxicology, 2023)
Objective Liver fibrosis is a chronic liver disease caused by a variety of pathophysiological. However, there are no effective treatments to combat it. HSCs are a major source of fibrotic cells and exploring the mechanisms of HSC activation may provide new strategies for the treatment of liver fibrosis. Objectives To explore the role and underlying mechanism of SLIT3 in HSCs fibrosis. Results GSE163211 dataset analysis identified aberrant expression of SLIT3 in NASH F1-F4 tissues and SLIT3 expression level was positively correlated with fibrosis-related proteins. In vitro experiments showed that TGF-β induced upregulation of SLIT3 in LX-2 cells. Knockdown of SLIT3 significantly inhibited TGF-β-induced α-SMA, COL1A2, and COL1A1 expression, inhibited excessive cell proliferation and migration, and suppressed YAP activity. Conclusion Collectively, our findings suggest that SLIT3 deficiency alleviates TGF-β-induced HSCs activation by inhibiting YAP activity.